Validation of a Commercial Glanders ELISA as an Alternative to the CFT in International Trade of Equidae - Elschner, Mandy Carolina; Melzer, Falk; Singha, Harisankar; Muhammad, Saqib; Gardner, Ian; Neubauer, Heinrich (Frontiers in Veterinary Science, 2021)
Glanders caused by Burkholderia (B.) mallei is a notifiable zoonotic disease in equidae. For international trade and movement of equids, certificates of negative serological test results for antibodies against B. mallei are required. To date, the complement fixation test (CFT) is the mandatory test to issue these health certificates. The CFT is difficult to standardize and, due to its poor specificity, often leads to false-positive reactions resulting in trade restrictions with considerable financial consequences. In the present study, the new ID Screen Glanders Double Antigen Multispecies ELISA (GLANDA- ELISA) (IDvet, Grabels, France) was evaluated using 400 negative and 370 glanders positive field samples of equidae. The GLANDA-ELISA was significantly more specific (99.8%) than the CFT (97.0%). Considering the comparable sensitivities of CFT (96.5 %) and ELISA (98.1%), this new GLANDA-ELISA test appears a suitable confirmatory test and is a realistic alternative for serological testing of horses for trade or movement.